Stroke Treatment Associated with Rehabilitation Therapy and Transcranial DC Stimulation (START-tDCS): a study protocol for a randomized controlled trial. Issue 1 (December 2016) - Andrade, Suellen; Santos, Natanael; Fernández-Calvo, Bernardino; Boggio, Paulo; Oliveira, Eliane; Ferreira, José; Sobreira, Amanda; Morgan, Felipe; Medeiros, Germana; Cavalcanti, Gyovanna; Gadelha, Ingrid; Duarte, Jader; et al.
Abstract Background Traditional treatment for motor impairment after stroke includes medication and physical rehabilitation. The transcranial direct current stimulation associated with a standard physical therapy program may be an effective therapeutic alternative for these patients. Methods This study is a sham-controlled, double-blind, randomized clinical trial aiming to evaluate the efficacy of transcranial direct current stimulation in activities of daily living and motor function post subacute stroke. In total there will be 40 patients enrolled, diagnosed with subacute, ischemic, unilateral, non-recurring stroke. Participants will be randomized to two groups, one with active stimulation and the other with a placebo current. Patients and investigators will be blinded. Everyone will receive systematic physical therapy, based on constraint-induced movement therapy. The intervention will be applied for 10 consecutive days. Patients will undergo three functional assessments: at baseline, week 2, and week 4. Neuropsychological tests will be performed at baseline and week 4. Adverse effects will be computed at each session. On completion of the baseline measures, randomization will be conducted using random permuted blocks. The randomization will be concealed until group allocation. Discussion This study will investigate the combined effects of transcranial direct current stimulation and physical therapy on functional improvement after stroke. We tested whether the combination of these treatments is more effective than physical therapy alone when administered in the early stages after stroke. Trial registration NCT02156635 - May 30, 2014. Randomization is ongoing (40 participants randomized as of the end of December 2015).